Masculinity among the Amish: Characteristics, Hegemony, and 'Soft Patriarchy' - Robert Strikwerda (The Journal of Amish and Plain Anabaptist Studies, 2020)
This article examines both Amish masculine cultural norms and practices and the characteristics of Amish men specifically as men. The first goal is to pull together information from the secondary literature on Amish men and masculinity. Salient characteristics or traits such as egalitarianism, pacifism, and rationality are discussed, and placed in the context of Gelassenheit (yieldedness), of the gender relations within families, and of Raewyn Connell’s notion of “hegemonic masculinity.” The second goal is to assess the appropriateness of general characterizations of the Amish gender regime, such as one with women as second-class citizens to men or as a “soft patriarchy.” It is argued that Amish society is better described as a “strong patriarchy” with a questionable gender power imbalance. Throughout, the intent is to show the mutual relevance of Amish Studies, Men’s Studies, and Women’s and Gender Studies. [Abstract by author.]